PRODUCTION DECISION RESCHEDULING OF PREFABRICATED BUILDING PARTS SUBJECT TO INTERFERENCE FROM THE ARRIVAL OF NEW ORDERS - Wang, Heping; Wang, Hui; Li, Yan; Wang, Fuyu (International Journal of Industrial Engineering: Theory, Applications and Practice, 2021)
Disruption events that occur during the production of prefabricated components present challenges for the feasibility of an original production plan. Therefore, rescheduling is of great significance in production management. In this paper, we study a rescheduling decision method for prefabricated building component production where the insertion of new orders is considered a disruption. We develop a rescheduling model for precast production to minimize the maximum completion time and design an improved grey wolf intelligent algorithm to solve the model. Furthermore, we take the initial plan as the base and establish a profit-loss function based on the saved time or the delay generated by the rescheduling plan. Finally, we conduct a case study that verifies the validity and feasibility of the rescheduling decision method and model. Our results contribute to the existing literature on rescheduling decisions by improving the stability of a production system.